Avelumab-Induced Scleroderma in a Patient with Metastatic Squamous Cell Carcinoma of the Lung - Jeffrey L. Dobrzynski; Blake E. Vest; Brian L. Swick (Case Reports in Dermatological Medicine)
Immune checkpoint inhibitors are associated with a spectrum of cutaneous immune-related adverse events. While maculopapular eruptions are the most common cutaneous adverse event, scleroderma can rarely develop. Herein, we report a case of new-onset scleroderma associated with avelumab treatment in the setting of metastatic squamous cell carcinoma of the lung. The pathophysiology of immune checkpoint inhibitor-induced scleroderma is not completely understood. A proposed mechanism is discussed along with the clinical presentation of symptoms and associated therapeutic response in cancer treatment. This case contributes to the few existing reports of immune checkpoint inhibitor-induced scleroderma to better understand the implications in the management of cutaneous immune-related adverse events.